PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE INSIDE OUTDSIDE CIRCLE (IOC) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS VC SD NEGERI 110 PEKANBARU - Metari Desinta; Eddy Noviana; Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The background of the problem in this research was the poor students’ achievements in social sciences, it can be seen on students’ social sciences scores. There were 19 of 35 students who had not achieved the Achievement Standard (54.28%), while the ones who achieved were only 16 students (45.71%), and the average scores of the class was 67.71. The Achievement Standard that school determines is 70. The method of research was classroom action research implemented in two cycles that consist of planning, action, observation, and reflection. Data were collected by observation technigue, test technigue and documentary technigue. The instrument of data collection used observation sheet and test student’s result . At the first meeting in cycle I, the percentage of teachers’ activity was 54.17% which is categorized as less. At the second meeting, the percentage increased to 62.50% which is categorized as enough. At the first meeting in cycle I, the percentage increased to 75.00% that is categorized as good. At the second meeting the percentage increased to 87.50% which is categorized as very good. The students’ activities had increased. At the first meeting in cycle I, the students’ activities gained 54.17% which is categorized as less, while at the second meeting in cycle I the students’ activities gained 62.50% which is categorized as enough. At the first meeting of cycle II, the percentage increased to 70.83% that is categorized as good, while at the second meeting the percentage increased to 95.83% which is categorized as very good. The average of students’ achievements before the implementation cooperative learning inside outside circle (IOC) type was 67.71 which increased to 73.14 in cycle I, and increased again to 80.57 in cycle II. The result of research showed that implementation cooperative learning inside outside circle (IOC) type can improve student’s result of social sciences.Keywords: Cooperative Learning inside outside circle (IOC) Type, Study Result,social sciences